2017
DOI: 10.1080/14767058.2016.1233397
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of birth weight discordance from fetal weight estimations at 21–24 weeks' scans in monochorionic and dichorionic twins

Abstract: Concordant EFWs at 21-24 weeks exclude discordant birth weight in monochorionic twins whereas discordant EFWs are poor predictors of birth weight discordance especially in dichorionic twins irrespective when the twins were born.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Conversely, other studies have found that secondtrimester ultrasound discordance in twins has poor predictive value for adverse perinatal outcomes, irrespective of chorionicity [1,[18][19][20]. Although in some investigations, second-trimester EFW discordance correlated with birth-weight discordance ≥20-25%, the predictive accuracy was low, thus preventing its wide practical clinical use [7,8]. Once malformations, chromosomal abnormalities, and TTTS were excluded, second-trimester ultrasound discordance was not significantly correlated with subsequent adverse outcomes [1,7,8].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Conversely, other studies have found that secondtrimester ultrasound discordance in twins has poor predictive value for adverse perinatal outcomes, irrespective of chorionicity [1,[18][19][20]. Although in some investigations, second-trimester EFW discordance correlated with birth-weight discordance ≥20-25%, the predictive accuracy was low, thus preventing its wide practical clinical use [7,8]. Once malformations, chromosomal abnormalities, and TTTS were excluded, second-trimester ultrasound discordance was not significantly correlated with subsequent adverse outcomes [1,7,8].…”
Section: Discussionmentioning
confidence: 92%
“…Although in some investigations, second-trimester EFW discordance correlated with birth-weight discordance ≥20-25%, the predictive accuracy was low, thus preventing its wide practical clinical use [7,8]. Once malformations, chromosomal abnormalities, and TTTS were excluded, second-trimester ultrasound discordance was not significantly correlated with subsequent adverse outcomes [1,7,8]. Moreover, in some studies, even after adjusting for monochorionicity, the predictive value of using either second-trimester EFW or AC discordance did not improve [1,19].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These methods have been extensively studied throughout the last decades. The majority of publications have reached the conclusion of poor sensitivity in predicting intertwin BW discordance [5,6,[9][10][11][12][13], however the performance is better when performed near delivery [7,8,[13][14][15]. Recently, Hehir et al [13] investigated the performance of ultrasound EFW in predicting intertwin BW discordance at different gestational ages.…”
Section: Accepted Manuscriptmentioning
confidence: 99%